Before and After COVID-19 Outbreak: Indonesia as a Successful Story of WHO Global Health Diplomacy - Candra, Ilham Agustian; Nurkhalisa, Shafiya (Center for Southeast Asian Social Studies (CESASS), 2023)
After the Spanish flu pandemic in 1920s, the world experienced another one named the COVID-19 pandemic in 2019. It has significantly impacted human life in various aspects. In response to this, not only countries but all actors in international relations take part including the World Health Organization (WHO). One of its moves was the formation of the ACT-Accelerator, which includes four pillars of COVID-19 management namely diagnostics, therapeutics, vaccines, and the health systems and response connector. In this case, WHO formed a multilateral cooperation called COVID-19 Global Access (COVAX). This collaboration incorporates several international organizations and agencies; namely, GAVI, CEPI, and UNICEF. COVAX aims to provide equal access for countries that need vaccines, especially developing countries. This study examines the global health diplomacy strategy carried out by the World Health Organization in procuring world vaccines through the COVAX program in Indonesia. The authors used a descriptive qualitative method with secondary sources to analyze the phenomenon in this study. Based on the conceptual framework, namely international organizations and global health diplomacy, the authors analyze the strategies pursued by WHO in realizing global health in Indonesia. This study found that the efforts of WHO global health diplomacy through the COVAX program to Indonesia include conducting vaccine research and development and raising funds and negotiating vaccine purchases. This study finally argues that the COVAX program serves as a concrete example of how WHO’s global health diplomacy strategies are implemented, offering a detailed case study of international cooperation in vaccine distribution.